Antianxiety Effect Of Methanolic Extract Of Bauhinia Racemosa (Lamk) Stem Bark In Mice - MRUNAL.S.DAVEY,; CLEMENT ATLEE.W,; S.R.S ASHOK BHARATHI,; MOHAMED FAROOK, (International Journal of Pharma and Bio Sciences, 2011)
This study was performed to investigate the anxiolytic-like effects of Methanolic extract of Bauhinia racemosa (MEBR) in mice using the elevated plus-maze model (EPM), light dark model, hole board test, foot shock induced freezing behavior. Furthermore, the anxiolytic-like effects of MEBR were compared to a known active anxiolytic drug (Diazepam). The extract administered orally in two different doses of 150mg/kg and 300mg/kg, was able to increase the time spent and the number of arm entries in the open arms of the elevated plus-maze, also increases the time spent by mice in the illuminated side of the light–dark test, showed significant increase in nose poking and decrease locomotion in hole board test, as well as caused significant reduction in freezing time in comparison with control animals. This effect was comparable to that of the benzodiazepine diazepam (2.0mg/kg p.o.). These results indicate that methanolic extract Bauhinia racemosa is an effective anxiolytic agent.